High strength, biodegradable and cytocompatible alpha tricalcium phosphate-iron composites for temporal reduction of bone fractures - Montufar, E B; Casas-Luna, M; Horynová, M; Tkachenko, S; Fohlerová, Z; Diaz-de-la-Torre, S; Dvořák, K; Čelko, L; Kaiser, J (Acta biomaterialia, 2018)
In this work alpha tricalcium phosphate (α-TCP)/iron (Fe) composites were developed as a new family of biodegradable, load-bearing and cytocompatible materials. The composites with composition from pure ceramic to pure metallic samples were consolidated by pulsed electric current assisted sintering to minimise processing time and temperature while improving their mechanical performance. The mechanical strength of the composites was increased and controlled with the Fe content, passing from brittle to ductile failure. In particular, the addition of 25 vol% of Fe produced a ceramic matrix composite with elastic modulus much closer to cortical bone than that of titanium or biodegradable magnesium alloys and specific compressive strength above that of stainless steel, chromium-cobalt alloys and pure titanium, currently used in clinic for internal fracture fixation. All the composites studied exhibited higher degradation rate than their individual components, presenting values around 200 μm/year, but also their compressive strength did not show a significant reduction in the period required for bone fracture consolidation. Composites showed preferential degradation of α-TCP areas rather than β-TCP areas, suggesting that α-TCP can produce composites with higher degradation rate. The composites were cytocompatible both in indirect and direct contact with bone cells. Osteoblast-like cells attached and spread on the surface of the composites, presenting proliferation rate similar to cells on tissue culture-grade polystyrene and they showed alkaline phosphatase activity. Therefore, this new family of composites is a potential alternative to produce implants for temporal reduction of bone fractures. STATEMENT OF SIGNIFICANCE: Biodegradable alpha-tricalcium phosphate/iron (α-TCP/Fe) composites are promising candidates for the fabrication of temporal osteosynthesis devices. Similar to biodegradable metals, these composites can avoid implant removal after bone fracture healing, particularly in young patients. In this work, α-TCP/Fe composites are studied for the first time in a wide range of compositions, showing not only higher degradation rate in vitro than pure components, but also good cytocompatibility and mechanical properties controllable with the Fe content. Ceramic matrix composites show high specific strength and low elastic modulus, thus better fulfilling the requirements for bone fractures fixation. A significant advance over previous works on the topic is the use of pulsed electric current assisted sintering together with α-TCP, convenient to improve the mechanical performance and degradation rate, respectively.
Keywords: modul pružnosti; fosforečnany vápenaté; lidé; osteoblasty; testování materiálů; fraktury kostí; Iron; Fractures, Bone; Bone Substitutes; Osteoblasts; Calcium Phosphates; Materials Testing; Ceramics; železo; Humans; kostní náhrady; keramika; nádorové buněčné linie; Elastic Modulus; Cell Line, Tumor